Investigation of Aluminum-Stainless Steel Dissimilar Weld Quality using Different Filler Metals - L. H., Shah; A. R., Razali; M., Ishak (Universiti Malaysia Pahang, 2013)
Aluminum-stainless steel dissimilar welding processes yield unwanted disadvantages in the weld joint due to the large difference between the aluminum-stainless steel sheets’ melting points and the nearly zero solid solubility between these two metals. Aluminum AA6061 and stainless steel SUS304 were lap-welded by using Metal Inert Gas (MIG) welding with aluminum filler ER5356 (Group 1) and stainless steel filler ER308LSi (Group 2). The effects of the welding voltage and type of filler metals used on the weld joints were studied. The welding voltage had a significant effect on the welding process, as higher voltage resulted in poorer appearance of the weld joint and led to defects for both groups, such as porosity and incomplete fusion. The microstructure for Group 1 joints shows enrichment of Si particles, which benefited the joint properties as it increased the strength of the metal. The stainless steel substrates that spread into the aluminum side are much greater in volume for Group 1 than for Group 2 joints. Meanwhile, the microstructure of Group 2 joints (using ER308LSi filler) consists of chromium carbide precipitation which yields a high hardness value, but a brittle structure. The hardness values of the welded seams in Group 1 and Group 2 range from 60 to 100 HV and 160 to 230 HV, respectively. The fracture in the tensile test yielded the highest tensile strength of 104.4 MPa with aluminum fillers. The tensile strength of Group 1 joints ranging from 47.8 to 104.4 MPa was collectively higher than Group 2 joints, between 20.24 to 61.76 MPa. Based on the investigation throughout this study, it can be concluded that the welding voltage of 18 V and aluminum filler ER5356 is the optimum filler in joining the dissimilar metals aluminum AA6061 and stainless steel SUS 304.